IPerforma Larva Lalat Tentara Hitam (Hermetia illucens) sebagai Biokonversi Limbah Industri Pengolahan Carica Dieng (Vasconcellea pubescens) di Wonosobo - Fatmanintyas, Irma; Ambarningrum, Trisnowati Budi; Atang, Atang; Haryanto, Trisno; Setiyono, Eko (Metamorfosa: Journal of Biological Sciences, 2022)
Waste in the form of skins and seeds originating from the Dieng carica ( Vasconcellea pubescens ) processing industry can be an environmental problem if not handled properly. BSF ( Hermetia illucens ) larvae as a bioconversion agent are expected to be a solution to this problem. The study was conducted experimentally using a completely randomized design (CRD) with 6 treatments and 4 replications including control treatment, P1 = 100% husk, P2 = 75% husk + 25% seed, P3 = 50% shell + 50% seed, P4 = 25% skin + 75% seeds, and P5 = 100% seeds. The observation time of the study was carried out for 21 days. The main parameters observed were the value of feed consumption and waste reduction index (WRI), while the supporting parameters were larval biomass, head capsule diameter and survival rate. The data obtained were analyzed using ANOVA with an error rate of 5%, and if the treatment had a significant, continued with the DMRT test with an error rate of 5%. The results of the study with various types of feed showed that the value of digested feed consumption by BSF larvae ranged from 60.42% - 81.26%. Meanwhile, the value of the waste reduction index ( WRI ) ranged from 2.82% - 3.73%. Waste reduction value of more than 50% indicates the effectiveness of BSF larvae in degrading organic waste. Thus the use of this type of feed in the form of feed using BSF larvae is effective in reducing the processing waste of Carica Dieng (V. pubescens).